Designing Crystalline/Amorphous NVNPF/NCK Cathode Toward High‐Performance Fully‐Printed Flexible Aqueous Rechargeable Sodium‐Ion Batteries (ARSIBs) - Hehe Ren; Jing Liang; Qun Liu; Yuanjie Wei; Wei Wu (Advanced Science)
Abstract The flexible ARSIBs have great potential in portable and wearable electronics due to their high cost‐effectiveness, safety, and amazing flexibility. Nevertheless, achieving both outstanding flexibility and high energy density remains a challenge. Herein, a battery‐supercapacitor composite material Na3V1.95Ni0.05(PO4)2F3/10%NC‐KOH (NVNPF/NCK) with coexistence of crystalline and amorphous phases is fabricated by loading nitrogenous carbon (NC) onto Na3V1.95Ni0.05(PO4)2F3 (NVNPF) and etching with KOH. It demonstrates high specific capacity (187.26 mAh g−1), ultrahigh energy density (262.16 Wh kg−1), and excellent cycle performance (the capacity retention is 81% at 1 C after 500 cycles). The high performance is achieved by doping Ni2⁺ loading NC and etching with KOH, which generates vacancy defects, enhances structural stability, and accelerates ion‐diffusion kinetics. Furthermore, the fully‐printed ARSIBs (F‐NTP//NVNPF/NCK) with high specific capacity (60.37 mAh g−1), amazing energy density (72.44 Wh kg−1), and excellent cycle performance, are fabricated using screen‐printing technique based on the NVNPF/NCK cathode and NaTi1.7Fe0.3(PO4)3 (F‐NTP) anode. To the best of the authors' knowledge, F‐NTP//NVNPF/NCK is the highest‐performing fully‐printed flexible ARSIB to date. In particular, these batteries can achieve tunability in shape and size, integration, and high‐throughput manufacturing. Thus, this work can offer greater possibilities for the development of high‐performance flexible ARSIBs.